Heart Failure with Preserved Ejection Fraction: An Enigma (Indian Journal of Public Health Research & Development, 2022)
Heart failure with preserved ejection fraction(HFpEF) is an entity showing an upward trend. The affected populationis rising on account of rise in the geriatric population as well as expanding incidence of comorbidities,thusunderlining the necessity of greater therapeutic avenues. The underlying disease mechanisms are complicated.Irrespective of EF, HFpEF negatively influences quality of life and hard clinical endpoints. Greater research intoHFpEF phenotypes, criteria for definition and improvement in prognosis is the need of the hour.
Keywords: HfpEF, diastolic function, sacubitril-valsartan